Social determinants of Health and Alcohol consumption in the UK (Epidemiology, Biostatistics, and Public Health, 2022)
Addressing the social determinants of health (SDH) and health inequities are essential for successfully combating alcohol-related harm. In U.K, excessive consumption of alcohol is a huge public health concern. An estimated 9 million adults drink at level that increase the risk of harm to their health; 1.6 million adults in England have some degree of alcohol dependence; and of these some 250,000 are believed to be moderately or severely dependent and may benefit from intensive specialist treatment. To be able to devise effective action, it is essential to comprehend these inequities in the healthcare system. Health inequities are not solely related to access to health care services; there are many other determinants related to living and working conditions, as well as the overall macro-policies prevailing in a country. The key intention of this review was to critically analyse the degree to which social determinants have impacted on excess alcohol consumption. A comprehensive approach to reduce inequities in alcohol-related harm requires action that includes mix of long- and short-term impacts, addressing the consequences and the root causes of inequities, and acting on both individuals and environments. Whereas, consequences of harmful alcohol use are more severe for those already experiencing social exclusion. We suggest that (1) the effective legislation, (2) modifying marketing strategies, (3) enhancing cooperation with regional organizations, (4) more effectively implementing existing regulation and (5) consulting expert will enhance SDH for this vulnerable population.